The effect of management accounting information systems, internal control, and information technology on managerial performance - Dila Arigra Putri; Wahyu Helmy Dimayanti Sukiswo (Indonesia Auditing Research Journal, 2026)
The purpose of this research is to examine how management performance at PT Varia Usaha Beton is affected by internal control, information technology, and management accounting information systems. The Partial Least Squares Structural Equation Modelling (PLS-SEM) technique, supported by SmartPLS 4 software, is used in this study's quantitative methodology. Using a saturated sampling strategy, the complete population 41 managers at PT Varia Usaha Beton was employed as the sample for this research. Questionnaires were used to collect data from respondents. With a significance value of 0.003, the findings demonstrate that management accounting information systems significantly and favourably impact managerial performance. Additionally, internal control significantly and favourably affects managerial performance, with a significance value of 0.004. With a significance value of 0.791, information technology has no discernible impact on managerial performance. These results show that effective internal control and high-quality management accounting information have a greater impact on improving managerial performance, whereas information technology has not made the best contribution when it has not been successfully incorporated into managerial tasks.